Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Pada Usaha Tani Jamur Tiram Arka di Kabupaten Probolinggo - Novita Lidyana; Dyah Ayu Perwitasari; Novi Itsna Hidayati (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2022)
This research is a type of quantitative research conducted on the "Arka" oyster mushroom farming business in Probolinggo district, East Java. Sources of data used are simple financial records of farm owners as secondary data sources and interviews with informants conducted to owners of "arka" oyster mushroom farms. Because it still uses estimated figures in its determination. So that this can lead to less accurate results of the total production costs incurred so that it has an impact on the profits or profits generated. Researchers found that within 3 months of harvesting, the cost of production was determined at Rp. 7,0671.33/kg with harvested production of Rp. 3,523 kg.